Propagação do pinhão manso por estaquia, enxertia e sementes - Furlani, Renata Capistrano Moreira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Jatropha can be propagated vegetatively by cuttings and grafting or by seeds. It is a allogamous plant, when propagated via seed originates progenies with high genetic variability, later production, but with developed tap root which gives great plant vigor and resistance to prolonged drought. When propagated vegetatively presents the same characteristics as the parental plant, just secondary roots were developed, but with early fruit production. The technique of grafting also gives more precocity to the plants, with the advantage of combining rootstock resistance with the graft yield. The present study aimed to develop techniques for Jatropha propagation by cuttings, grafting and seed systems. Four experiments were conducted, and the first one aimed to test the rooting and vegetative development of plants from different types of cuttings (basal, middle and apical) on two types of substrates (sand and vermiculite). The second evaluated the rooting of cuttings (basal, middle and apical) from branches stored in ambient conditions for 30 and 60 days. The third experiment aimed to evaluate the antioxidant effect of citric acid in cuts before grafting and the use of two systems for setting grafts string and gauze. The last experiment evaluated seed germination and early seedling development of Jatropha as a function of environment and time of seed storage.When propagated by cuttings and using different substrates for rooting, Jatropha basal cuttings provide a higher percentage of living cuttings, as well as cuttings installed in vermiculite also had a higher percentage of survival. At the end of the experiment the basal cuttings were superior to others in all variables analyzed, as well as those in vermiculite. Regarding storage of Jatropha branches for later use, it is concluded that the storage of Jatropha branches up to 30 days is feasible under the conditions studied andthe basal part of the cuttings ...

O pinhão manso pode ser propagado de forma vegetativa através de estacas e enxertia ou via seminífera. Por ser uma planta de polinização cruzada, quando propagado via sementes origina indivíduos com alta variabilidade genética, produção mais tardia, no entanto com desenvolvimento de raiz pivotante, o que confere às plantas maior vigor e resistência a secas prolongadas. Quando propagado vegetativamente apresenta as mesmas características da planta mãe, desenvolvem apenas raízes secundárias, e são mais precoces na produção de frutos. A técnica da enxertia também confere maior precocidade às plantas enxertas, com a vantagem de poder combinar resistência do porta enxerto com produtividade do enxerto. O presente trabalho teve como objetivo desenvolver técnicas de propagação para pinhão manso através de estacas, sistemas de enxertia e sementes. Foram desenvolvidos 4 experimentos, sendo que o primeiro experimento avaliou o pegamento por meio de avaliações do desenvolvimento vegetativo de diferentes tipos de estacas (basal, mediana e apical) de pinhão manso em dois tipos de substratos (areia e vermiculita). O segundo avaliou o enraizamento de estacas (basal, mediana e apical) provenientes de ramos armazenados em condições ambientes por 30 e 60 dias. O terceiro experimento objetivou avaliar o efeito do antioxidante ácido cítrico nos cortes antes da realização da enxertia e o uso de dois sistemas de fixação dos enxertos, barbante e gaze. O último experimento avaliou a germinação de sementes e o desenvolvimento inicial de plântulas de pinhão manso em função do ambiente e do tempo de armazenamento das sementes. Quando propagado por estacas e utilizando diferentes substratos para enraizamento, as estacas basais de pinhão manso proporcionam uma maior porcentagem de estacas vivas, assim como estacas instaladas em vermiculita também apresentaram uma maior porcentagem de ...
Keywords: Plantas - Propagação; Pinhão-manso - Propagação por estaquia; Enxertia; Sementes; Plant propagation